Assessing the impact of turnip yellows virus infection and drought on canola performance: implications under a climate change scenario - Lago, Clara; Fereres, Alberto; Moreno, Aránzazu; Trębicki, Piotr (Frontiers in Agronomy, 2024)
IntroductionCanola (Brassica napus L.) is one of the most important crops worldwide. Turnip yellows virus (TuYV), transmitted by aphids, is one of the most damaging viruses affecting canola crops and is challenging to control. With the prediction of more intense and prolonged drought events due to future climate change, an additional factor may extensively impact the epidemiology of plant diseases. This study aimed to understand the impact of drought on canola plants infected with TuYV and to explore the relationship between virus infection and drought.MethodsTwo glasshouse experiments were conducted: 1. Competition: Four plants (two infected, two non-infected) were grown in the same pot. 2. No Competition: One plant was grown per pot. In both experiments, infected and non-infected canola plants were exposed to well-watered conditions, water stress (simulated drought), and terminal drought. Various plant traits were recorded, including biomass, leaf area, height, number of leaves, chlorophyll content, water use efficiency, and virus symptom expression.ResultsBoth virus infection and water stress reduced dry biomass, leaf area, and height. Virus infection alone reduced canola biomass by up to 49% compared to non-infected, well-watered controls. Under water stress or terminal drought, the biomass of TuYV-infected plants was further reduced by up to 71% and 65%, respectively. Virus infection also reduced the number of leaves, although water treatment alone did not. Chlorophyll content was higher in water-stressed and terminal drought plants compared to well-watered ones, while virus infection reduced chlorophyll content. The impact of drought and virus infection was more pronounced when plants were under competition.DiscussionGiven the expected increase in prolonged and frequent droughts in many canola-growing regions due to climate change, a significant detrimental effect on canola production due to the combined influence of drought and TuYV is anticipated. This study underscores the need for developing mitigation strategies to protect canola production in a changing climate.